2021
DOI: 10.1007/s11356-021-12384-0
|View full text |Cite
|
Sign up to set email alerts
|

Fuel subsidies and carbon emission: evidence from asymmetric modelling

Abstract: It is expected that fuel subsidy removal should hinder carbon emissions growth through low energy consumption channels amid higher energy prices. However, outliers in this theoretical disposition make empirical proof of the fuel subsidy-carbon intensity apt and primitive. Despite established fuel subsidy abolishment gains for climate and economic welfare, the relevance, magnitude and policy implications remain dimly. This paper employs the non-linear autoregressive distributed lag (NARDL) estimation procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…Increased investment in energy exploration facilities within the terrain of resource-rich nations could block leakages along the entire oil exploration value chain (Adekunle and Oseni, 2021). African resource-rich nations should look inward at their use and management of factor endowment.…”
Section: Conclusion Implications Limitations and Suggestions For Furt...mentioning
confidence: 99%
“…Increased investment in energy exploration facilities within the terrain of resource-rich nations could block leakages along the entire oil exploration value chain (Adekunle and Oseni, 2021). African resource-rich nations should look inward at their use and management of factor endowment.…”
Section: Conclusion Implications Limitations and Suggestions For Furt...mentioning
confidence: 99%
“…In a related paper 11 demonstrated that a rise in fossil fuel subsidies generates an expansion in ecological footprint in developing countries for the period, 2010-2017. 12 suggested that the removal of fuel subsidy is inversely associated with CO 2 emissions in a developing economy for the period, 1980-2018. There are at least three possible hypotheses on the relationship between transportation subsidies and CO 2 emissions in the transport sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results suggest that reduction in fossil fuel subsidies generate a decrease in CO 2 emissions. In a related paper 11 demonstrated that a rise in fossil fuel subsidies generates an expansion in ecological footprint in developing countries for the period, 2010–2017 12 . suggested that the removal of fuel subsidy is inversely associated with CO 2 emissions in a developing economy for the period, 1980–2018.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations